Comparing the role of site disturbance and landscape properties on understory species richness in fragmented periurban Mediterranean forests - Guirado, Maria; Pino, Joan; Rodà, Ferran (Landscape Ecology, 2007)
We hypothesized that the spatial con- ﬁguration and dynamics of periurban forest patches in Barcelona (NE of Spain) played a minor role in determining plant species richness and assemblage compared to site conditions, and particularly to both direct (measured at plot level) and potential (inferred from landscape metrics) human-associated site disturbance. The presence of all understory vascular plants was recorded on 252 plots of 100 m 2 randomly selected within forest patches ranging in size from 0.25 ha to 218 ha. Species were divided into 6 groups, according to their ecology and conservation status. Site condition was assessed at plot level and included physical attributes, human-induced disturbance and Quercus spp. tree cover. Landscape structure and dynamics were assessed from patch metrics and patch history. We also calculated a set of landscape metrics related to potential human accessibility to forests. Results of multiple linear regressions indicated that the variance explained for non-forest species groups was higher than for forest species richness. Most of the main correlates corresponded to site disturbance variables related to direct human alteration, or to landscape variables associated to indirect human effects on forests: Quercus tree cover (a proxy for successional status) was the most important correlate of non-forest species richness, which decreased when Quercus tree cover increased. Human-induced disturbance was an important correlate of synanthropic and total species richness, which were higher in recently managed and in highly frequented forests. Potential human accessibility also affected the richness of most species groups. In contrast, patch size, patch shape and connectivity played a minor role, as did patch history. We conclude that human inﬂuence on species richness in periurban forests takes place on a small scale, whereas large-scale effects attributable to landscape structure and fragmentation are comparatively less important. Implications of these results for the conservation of plant species in periurban forests are discussed.
Keywords: Forest condition; Forest fragmentation; Forest patches; Human-induced disturbance; Multiple linear regressions; Patch history; Plant species richness; Synanthropic species

Comparing the role of site disturbance and landscape properties on understory species richness in fragmented periurban Mediterranean forests - Guirado, Maria; Pino, Joan; Rodà, Ferran (Landscape Ecology, 2007)
We hypothesized that the spatial con- ﬁguration and dynamics of periurban forest patches in Barcelona (NE of Spain) played a minor role in determining plant species richness and assemblage compared to site conditions, and particularly to both direct (measured at plot level) and potential (inferred from landscape metrics) human-associated site disturbance. The presence of all understory vascular plants was recorded on 252 plots of 100 m 2 randomly selected within forest patches ranging in size from 0.25 ha to 218 ha. Species were divided into 6 groups, according to their ecology and conservation status. Site condition was assessed at plot level and included physical attributes, human-induced disturbance and Quercus spp. tree cover. Landscape structure and dynamics were assessed from patch metrics and patch history. We also calculated a set of landscape metrics related to potential human accessibility to forests. Results of multiple linear regressions indicated that the variance explained for non-forest species groups was higher than for forest species richness. Most of the main correlates corresponded to site disturbance variables related to direct human alteration, or to landscape variables associated to indirect human effects on forests: Quercus tree cover (a proxy for successional status) was the most important correlate of non-forest species richness, which decreased when Quercus tree cover increased. Human-induced disturbance was an important correlate of synanthropic and total species richness, which were higher in recently managed and in highly frequented forests. Potential human accessibility also affected the richness of most species groups. In contrast, patch size, patch shape and connectivity played a minor role, as did patch history. We conclude that human inﬂuence on species richness in periurban forests takes place on a small scale, whereas large-scale effects attributable to landscape structure and fragmentation are comparatively less important. Implications of these results for the conservation of plant species in periurban forests are discussed.
Keywords: Forest condition; Forest fragmentation; Forest patches; Human-induced disturbance; Multiple linear regressions; Patch history; Plant species richness; Synanthropic species

Quercus and Pinus cover are determined by landscape structure and dynamics in peri-urban Mediterranean forest patches - Guirado, Maria; Pino, Joan; Rodà, Ferran; Basnou, Corina (Plant Ecology, 2007)
Successional dynamics in Mediterranean forests have been modulated by anthropogenic disturbances during thousands of years, especially in areas densely populated since ancient times. Our objective is to determine whether pine tree cover (early-successional species) and oak tree cover (late-successional species), used as a surrogate of successional stage of peri-urban fragmented forests in the Valle`s lowlands (Catalonia, NE, Spain), are primarily determined by (1) climate and topography; (2) anthropogenic disturbances; (3) patch structure; or (4) patch dynamics from 1956 to 1993. Quercus spp. and Pinus spp. tree cover were separately recorded on 252 randomly selected plots of 100 m 2 , within forest patches ranging in size from 0.25 to 218 ha. Multiple linear regressions indicated that forest patch history is the most important variable determining oak and pine tree cover: new forest patches showed higher pine and lower oak tree cover than recently split patches (i.e. those that became fragmented from large forest areas after 1956). Patches already existing as such in 1956 (pre-existent patches) showed higher pine cover than recently split patches. Oak cover increased and pine cover decreased with increasing forest connectivity of the patch. Finally, highly frequented forests were related to high cover of pines. Climatic and topographic variables were not signiﬁcant. We conclude that pine and oak cover in these peri-urban forests are mainly determined by recent patch dynamics, but also by the spatial pattern of patches. However, humaninduced disturbance can modulate this as there is some evidence for pine being associated with a high human frequentation.
Keywords: á pinus; á quercus forests; anthropogenic disturbances; anthropogenic disturbances á forest; Forest fragmentation; forests á patch structure; fragmentation á historical dynamics; historical dynamics; patch structure; pinus forests; Quercus forests